Dating of a ring on one of the largest known Roman iron anchors (La Grande-Motte, France): Combined metal and organic material radiocarbon analysis. (December 2022) - Berthaut-Clarac, Sébastien; Nantet, Emmanuel; Leroy, Stéphanie; Delqué-Količ, Emmanuelle; Perron, Marion; Adam, Pierre; Schaeffer, Philippe; Kerfant, Céline
Highlights: Radiocarbon analysis dating the largest iron anchors to the early imperial period. Find spot evidences the use of the Aigues-Mortes Bay for mooring in antiquity. Ropes impregnated with pitch (puddening) found on one anchor protected the cable from chafing. Provides a methodology for the dating of anchors found out of archaeological context. Abstract: Underwater operations conducted along the southern French coast have unveiled two large, isolated anchors of iron. The largest ever found in the ancient Mediterranean, they reveal that Roman merchantmen moored in Aigues-Mortes Bay. A combination of analyses focusing on the ring, which belonged to one of the two anchors, offered the opportunity to collect data from isolated anchors and to document their production. Radiocarbon analysis, conducted for the first time on this type of object, determined that they were manufactured in the early imperial period. Another key discovery was a layer of fibers found in a concretion from the ring, which revealed rare remnants of ropes impregnated with pitch that could correspond to puddening. The replication of similar analyses on rings belonging to other anchors would provide a better understanding of this crucial component for ancient mooring.